Internal kinematics of multiple stellar populations in globular clusters. Issue Volume 14:Issue S351(2019) (May 2019) - Libralato, Mattia
Abstract: Spectroscopy and photometry have revealed existence, complexity and properties of the multiple stellar populations (mPOPs) hosted in Galactic globular clusters. However, the conundrum of the formation and evolution of mPOPs is far from being completely exploited: the available pieces of information seem not enough to shed light on these topics. Astrometry, and in particular high-precision proper motions, can provide us the sought-after answers about how mPOPs formed and have evolved in these ancient stellar systems. In the following, I present a brief overview of the observational results on the internal kinematics of the mPOPs in some GCs thanks to Hubble Space Telescope high-precision proper motions.